Benefits of the inoculated canavalia intercropped with mycorrhizal fungi and Rhizobium in Coffea canephora - Bustamante-González, Carlos Alberto (2022)
Introduction. Coffee growing requires technologies that increase yields, fertilizer use efficiency , promote the use of local sources of nutrients and take advantage of the benefits of microorganisms. Objetive. To establish the feasibility of the intercropping canavalia inoculated with rhizobia and arbuscular mycorrhizal fungi on coffee trees and their relationship with nitrogen fertilization. Materials and methods. The study was carried out between 2008 and 2012 at the Instituto de Investigaciones Agro-Forestales , in Santiago de Cuba, Cuba. A randomized block design with factorial arrangement was applied. Five nitrogen fertilization systems were studied, with and without inoculated canavalia in a pruned coffee plantation cultivated in Cambisol. The canavalia plants were maintained in the coffee tree lanes during the rainy season, in growth cycles of 90 at 120 days, cutting, mulching and subsequent sowing. The canavalia seeds were coated with mycorrhizae and Rhizobium inoculants and sown at 25 cm x 25 cm in the rows of the coffee trees. The biomass, legume growth, coffee yield and agronomic efficiency of nitrogen fertilization were evaluated. Results. With the canavalia inoculated with Rhizobium and mycorrhizal fungi, 205.9 kg of N ha-1 were incorporated in three years and coffee yield increased by 17 % and 16 % in the first and second year, respectively. With the N4 + canavalia fertilization system, an average annual yield of 1.69 t ha-1 of gold coffee was obtained. Conclusions. The intercropping of canavalia with the coffee tree increased the efficiency of nitrogen fertilization. The intercropping of canavalia inoculated with Rhizobium and mycorrhizae in the management of C. canephora during the first two years from the low pruning of the coffee tree.